When connectedness increases hemispatial neglect. - Tian, Y; Huang, Y; Zhou, K; Humphreys, G; Riddoch, M; Wang, K (Public Library of Science, 2011)
Patients with left neglect were tested with "chimeric" figures composed of the right and left halves of two different objects. The connectivity relation was modulated between the two half figures. For some displays, the two chimeric halves were separated by a small gap, while in others, the separate halves were connected by a line segment. In line with previous reports, performance on reporting the left half improved when the chimera were separated; but when a line connected the two separated halves the advantage was lost. If the connecting line was broken, the performance was again enhanced. The results suggest an important role for connectedness in the representation of perceptual objects and in the distribution of attention in neglect.